A 5G graphene antenna produced by screen printing method - Siti Nor Hafizah Sa’don; Mohd Haizal Jamaluddin; Muhammad Ramlee Kamarudin; Fauzan Ahmad; Samsul Haimi Dahlan (Institute of Advanced Engineering and Science, 2019)
The save and fast manufacturing are required in order to achieve 5G technology. However, there are many kinds of manufacturing antenna which are depending on material applied in the antenna itself. Each type of manufacturing also has its own advantages and drawback. In this article, a graphene antenna for 5G applications is manufactured using screen printing method. A fine mesh resolution of 120 µm is used to print the antenna accurately. This kind of printing has capability to produce antenna in less than 5 minutes. The antenna made by conductive graphene ink has size of 11.8 x 12.2 x 0.076 mm3 and produced within a small amount of graphene ink. The measured antenna resonates at 15.04 GHz with reflection coefficient magnitude of -12.05 dB and percentage of impedance bandwidth is 30 % which is in the range of 13.3 to 18.0 GHz. The radiation pattern at E-plane and H-plane of the graphene antenna are simulated and measured where the result obtained are comparable.